Strategi Pengelolaan Sumber Daya Manusia pada Generasi Z Tantangan dan Peluang di Era Digital Untuk Meningkatkan Kematangan Karir - Aprilita, Aprilita (Advances In Social Humanities Research, 2024)
The importance of adapting human resource management (HRM) strategies becomes increasingly fundamental in the rapid development of technology and changing workforce needs in this digital era. The objective of this research is to explore how HRM strategies can be adapted to meet the challenges and opportunities faced by Generation Z in the digital era, with a focus on enhancing career maturity. Additionally, the aim is to identify key factors in the effective implementation of HRM strategies for Generation Z that contribute positively to career maturity in the digital era. In the research titled "Human Resource Management Strategies for Generation Z: Challenges and Opportunities in the Digital Era for Career Maturity Enhancement," a qualitative approach can be a highly relevant method to provide in-depth understanding of the dynamics between HRM strategies, challenges faced by Generation Z, and career maturity improvement. The research findings indicate that personalized career development plans are an effective strategy to meet the individual needs of Generation Z, considering their preference for recognition of each individual's uniqueness. Through this personalization, organizations can build stronger bonds with employees and create more meaningful experiences.